Regional differences in sorafenib‐treated patients with hepatocellular carcinoma: GIDEON observational study. (1st April 2016) - Kudo, Masatoshi; Lencioni, Riccardo; Marrero, Jorge A.; Venook, Alan P.; Bronowicki, Jean‐Pierre; Chen, Xiao‐Ping; Dagher, Lucy; Furuse, Junji; Geschwind, Jean‐Francois H.; Ladrón de Guevara, Laura; Papandreou, Christos; Sanyal, Arun J.; et al.
Abstract: Background & Aims: Treatment approaches for hepatocellular carcinoma (HCC) vary across countries, but these differences and their potential impact on outcomes have not been comprehensively assessed. Data from the multinational GIDEON (Global Investigation of therapeutic DEcisions in HCC and Of its treatment with sorafeNib) registry evaluated differences in patient characteristics, practice patterns and outcomes in HCC across geographical regions in patients who received sorafenib. Methods: GIDEON is a non‐randomised, observational registry study conducted in 39 countries across five global regions. HCC patients in whom a decision to treat with sorafenib was made in clinical practice and according to local practices were included. Results: 3202 patients were evaluable for safety analysis: Asia‐Pacific ( n = 928), Japan ( n = 508), Europe ( n = 1113), USA ( n = 563) and Latin America ( n = 90). Patients in Japan had earlier‐stage disease at initial diagnosis compared with patients in other regions (Barcelona Clinic Liver Cancer stage A; 43.7% vs 9.1–24.3%). Use of locoregional therapies before sorafenib, including transarterial chemoembolisation, was more common in Japan (84.4%) and Asia‐Pacific (67.2%) compared with the USA (49.4%) and Europe (43.5%). Treatment patterns with respect to sorafenib also differed, with a shorter duration of treatment reported in the USA and Asia‐Pacific. Time from initial diagnosis to death was longer in Japan compared with other regions (median, 79.6 months vs 14.8–25.0 months). Conclusions: Data from GIDEON highlight regional variations in the management of HCC and patient outcomes. Greater standardisation of management may help optimise outcomes for HCC patients.